Quality of Work Life as a Mediator on the Impact of Work-Life Balance on Job Satisfaction - Vano Halal Marga Pratama; Veronika Agustini Srimulyani (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2022)
Work-life Balance (WLB) can affect employee attitudes in the company, such as job satisfaction (JS) and also have an effect on the quality of work-life (QWL). This study aims to test and analyze the significance of the direct and indirect influence of WLB on JS through QWL as a mediator, by taking the object of PT KAI (Persero) Daop 7 Madiun employees. The research approach is quantitative. The primary data used in the study were obtained from a questionnaire on research variables distributed to 115 employees of PT KAI (Persero) Daop 7 Madiun as a research sample. The sampling technique used is proportionate stratified random sampling. Data analysis using path analysis, processed with SPSS and Sobel Test software. The results of empirical studies show that: 1) WLB can significantly increase JS; 2) WLB can significantly improve the QWL; 3) QWL can significantly increase JS; 4) QWL partially mediates the effect of WLB on JS.